Hubungan Antara Pelatihan Berkuda dengan Perkembangan Motorik Kasar Anak di Surabaya - Aini, Destia Habibah Nur; Lestari, Gunarti Dwi (J+PLUS UNESA, 2023)
Training is one type of non-formal education that aims to develop behavior in terms of knowledge, skills and attitudes. One of the trainings that are in vogue, especially among children, is horse riding training. A training that is considered capable of developing gross motor skills in children. The purpose of this study was to examine and determine whether there is a relationship between horse riding training on children's gross motor development. This study used a quantitative method. The design in this study used a pretest-posttest with data collection techniques using action tests, questionnaires, and documentation. While the data analysis techniques used are validation test, reliability test, normality test, and hypothesis testing using product moment. The results showed that there is a significant relationship between horse riding training and children's gross motor development. The results of the data calculation are r count shows the result of 0.673 and t count of 4.8147 so from these results it can be concluded that Ha is accepted and Ho is rejected, based on these calculations it can be said that there is a relationship between horse riding training and children's gross motor development in Surabaya.